Bioakumulasi Logam Cd, Cu, Pb dan Zn Pada Beberapa Bagian Tubuh Ikan Gulama (Sciaena ruselli) dari Perairan Dumai, Riau - Nurrachmi, Irvina; Amin, Bintal; Habibi, Muhammad Nudi (UNIVERSITAS SRIWIJAYA, 2011)
Determination of heavy metal concentrations (Cd, Cu, Pb and Zn) inÃ‚Â different parts (muscle, bone, scale, intestine, gills and fin) of a croacker fish (S. russelli) collected from Dumai coastal waters were carried out during May to July 2009. The concentration of each metal was determined by AtomicAbsorption Spectrophotometer Perkin Elmer 3110 in the Marine Chemistry Laboratory, Marine Science Department University of Riau Pekanbaru. The results showed that Zn was found to be the highest concentrations in most of the fish body parts analyzed followed by Pb, Cu and Cd in both samples from the western and eastern regions of Dumai coastal waters. In general, the concentrations of all metals analyzed in the present study were higher in fish collected from the eastern region of Dumai coastal waters where more anthropogenic activities such as industries and human habitations along the coastal area were found. The concentration of heavy metals observed were Cd:Ã‚Â 0.098 Ã¢â‚¬â€œ 0.103, 0.189 Ã¢â‚¬â€œ 0.283, 0.099 Ã¢â‚¬â€œ 0.289, 0.107 Ã¢â‚¬â€œ 0.302, 0.182 Ã¢â‚¬â€œ 0.377 and 0.118 Ã¢â‚¬â€œ 0.397; Cu: 0.130 Ã¢â‚¬â€œ 0.198, 0.189 Ã¢â‚¬â€œ 0.341, 0.082 Ã¢â‚¬â€œ 0.073, 0.132 Ã¢â‚¬â€œ 0.285, 0.520 Ã¢â‚¬â€œ 0.746 and 0.175 Ã¢â‚¬â€œ 0.337; Pb:Ã‚Â 3.979 Ã¢â‚¬â€œ 4.109, 4.144 Ã¢â‚¬â€œ 4.601, 0.970 Ã¢â‚¬â€œ 2.527, 2.853 Ã¢â‚¬â€œ 4.367, 5.053 Ã¢â‚¬â€œ 7.074 and 4.637 Ã¢â‚¬â€œ 6.262 and Zn:Ã‚Â 5.713 Ã¢â‚¬â€œ 5.755, 7.956 Ã¢â‚¬â€œ 8.558, 4.649 Ã¢â‚¬â€œ 6.232, 5.730 Ã¢â‚¬â€œ 7.745, 8.988 Ã¢â‚¬â€œ 11.115 and 8.777 Ã¢â‚¬â€œ 10.686 Ã‚Âµg/g for muscle, bone, scale, intestine, gills and fins respectively. Concentrations of heavy metals in each body part of the fish were as follow: fin > gills > intestine > scale > bone > muscle for Cd; gills >Ã‚Â bone > fin > intestine > muscle > scale for Cu; gills > Fin > bone > intestine > muscle > scale for Pb and gills > fin > bone > intestine > scale > muscle for Zn. The concentrations of heavy metals in muscle were lower than other analyszed organs in the present study and this was considered to be an advantageous from the human health points of view as because muscle constitute the greatest mass of the fish that is consumed.